Mechanical complications of acute myocardial infarction - a review of current literature - Gawin, Konrad; Zawiślak, Wiktoria; Ignasiak, Anita; Cisowski, Michał; Dąbrowska, Maria; Rychlica, Kacper; Cholewińska-Rychlica , Jolanta; Madura, Paulina; Mrozik-Gałecka, Daria (Quality in Sport, 2026)
Mechanical complications of acute myocardial infarction (AMI) include papillary muscle rupture and acute mitral regurgitation, ventricular septal rupture, free wall rupture and pseudoaneurysm. The incidence of mechanical complications of AMI has decreased significantly in the era of widespread early reperfusion and primary percutaneous intervention, but they are still associated with high mortality. Diagnosis and prompt implementation of interventions (hemodynamic stabilization, surgical, transcatheter) remain crucial for survival. However, due to the small number of high-quality clinical trials, the quality of care often depends on local procedures and resources. This review article summarizes the available data on the main mechanical complications after AMI, based on the latest guidelines and current review articles and studies from 1991 to 2022.